Malaysian brown macroalga Padina australis mitigates lipopolysaccharide-stimulated neuroinflammation in BV2 microglial cells - Kogilavani, Subermaniam; Lew, Sze Yuen; Yow, Yoon Yen *; Lim, Siew Huah; Yu, Wing Shan; Lim, Lee Wei; Wong, Kah Hui (Mashlad University of Medical Sciences, 2023)
Objective(s): Neuroinflammation and microglial activation are pathological features in central nervous system disorders. Excess levels of reactive oxygen species (ROS) and pro-inflammatory cytokines have been implicated in exacerbation of neuronal damage during chronic activation of microglial cells. Padina australis, a brown macroalga, has been demonstrated to have various pharmacological properties such as anti-neuroinflammatory activity. However, the underlying mechanism mediating the anti-neuroinflammatory potential of P. australis remains poorly understood. We explored the use of Malaysian P. australis in attenuating lipopolysaccharide (LPS)-stimulated neuroinflammation in BV2 microglial cells.